Investigation of Material Compatibility for Embedding Stereolithography - Rechtenwald, Thomas; Kopczynska, Agnieszka; Schmachtenberg, Ernst; Devrient, Martin; Frick, Thomas; Schmidt, Michael (Proceedings of the Conference Multi-Material Micro Manufacture 4M, 2008)
Decreasing sales figures and increasing demand of different variants at the same time, as well as the desire of a short time to market pose a challenge for nowadays manufacturing technology. In this context, a new flexible production technology for mechatronical devices, which include also optical functions, called Embedding Stereolithography (eSLA) is introduced. eSLA combines the flexibility to automatically generated inner and outer complex geometries of conventional SLA with embedded functional components, which are conducted by generative manufactured electrical and/or optical structures. To form a rugged mechatronical device out of mechanic and/or electronic parts by eSLA a sufficient wetting of the used components by the processed liquid photopolymer is needed. Therefore the surface tension and viscosity of different photopolymers is measured and compared to surface energies and surface roughness of relevant component materials. Afterwards the characteristics of wetting of the chosen photopolymers on these materials are discussed.<br
Keywords: Rapid Prototyping; mechatronics